Labor Regulation and Employment in India's Retail Stores - Amin, Mohammad (World Bank, Washington, DC, 2012)
A new dataset of 1,948 retail stores in India compiled by the World Bank's Enterprise Surveys shows that 27 percent of the stores report labor regulations as a problem for their business. Using these data we analyze the effect of labor regulation on employment at the store level. We find that stricter labor regulation has a strong negative effect on employment. Our estimates show that labor reforms are likely to increase employment by 22 percent of the current level for an average store.